Autologous hematopoietic stem-cell transplantation in neurological disorders: current approach and future directions. (1st December 2020) - Das, Joyutpal; Sharrack, Basil; Snowden, John A
ABSTRACT: Introduction: Autologous hematopoietic stem-cell transplantation (AHSCT) has become increasingly popular in recent years as an effective treatment of immune-mediated neurological diseases. Treatment-related mortality has significantly reduced primarily through better patient selection, optimization of transplant technique, and increased center experience. Area covered: Multiple sclerosis is the main indication, but people with neuromyelitis optica spectrum disorder, stiff-person spectrum disorder, chronic inflammatory demyelinating polyneuropathy, myasthenia gravis, and other immune-mediated neurological disorders also have been treated. The review herein discusses the use of AHSCT in these neurological disorders, the importance of patient selection and transplant technique optimization and future directions. Expert opinion: Phase II and III clinical trials have confirmed the safety and efficacy of AHSCT in multiple sclerosis and recent phase II clinical trials have also suggested its safety and efficacy in chronic inflammatory demyelinating polyneuropathy and neuromyelitis optica spectrum disorder, with the evidence in other neurological disorders limited to individual case reports, small case series, and registry data. Therefore, further randomized controlled clinical trials are required to assess its safety and efficacy in other neurological conditions. However, in rare neurological conditions, pragmatic treatment trials or registry-based studies may be more realistic options for gathering efficacy and safety data.